ANALISIS PENDAPATAN PENGUSAHA BATU BATA DI DUSUN PELABU DESA KURIPAN SELATAN KECAMATAN KURIPAN KABUPATEN LOMBOK BARAT - Mimi Cahayani; Baehaqi, Baehaqi; Sarifah, Sarifah; Baiq Rizka Milania Ulfah (Jurnal Kompetitif : Media Informasi Ekonomi Pembangunan, Manajemen dan Akuntansi, 2024)
This study aims (1) to find out and describe how brick entrepreneurs in Pelabu Hamlet, South Kuripan Village, Kuripan District, West Lombok Regency, manage land area, (2) to find out and describe how brick entrepreneurs in Pelabu Hamlet, South Kuripan Village, Kuripan District, West Lombok Regency, manage capital, (3) to find out and describe how brick entrepreneurs in Pelabu Hamlet, South Kuripan Village, Kuripan District, West Lombok Regency, manage labor, (4) to find out and describe how brick entrepreneurs in Pelabu Hamlet, South Kuripan Village, Kuripan District, West Lombok Regency, manage production, (5) to find out and describe how brick entrepreneurs in Pelabu Hamlet, South Kuripan Village, Kuripan District, West Lombok Regency, manage marketing, (6) and to find out and describe how brick entrepreneurs in Pelabu Hamlet, South Kuripan Village, Kuripan District, West Lombok Regency, manage income. The type of research used is qualitative research with a descriptive approach. Data collection techniques used are Observation, Interviews and Documentation. The results of this study indicate that the income of brick entrepreneurs is greatly influenced by the price of raw materials, production costs, selling prices of bricks and market demand. In addition, external factors such as weather conditions.